FCS of superconducting tunnel junctions in nonequilibrium - Soller, Henning (International journal of modern physics. B, Condensed matter physics etc., 2013)
We analyze the full counting statistics (FCS) of a superconducting junction in nonequilibrium in the limit of small interface transparency. In this limit we treat both supercurrent and multiple And...